Kinetics of amphiphile association with two-phase lipid bilayer vesicles. - Pokorny, A (2000)
We examined the consequences of membrane heterogeneity for the association of a simple amphiphilic molecule with phospholipid vesicles with solid-liquid and liquid-liquid phase coexistence. To address this problem we studied the association of a single-chain, fluorescent amphiphile with dimyristoylphosphatidylcholine (DMPC) vesicles containing varying amounts of cholesterol. DMPC bilayers containing 15 mol% cholesterol show a region of solid-liquid-ordered (s-l(o)) coexistence below the T(m) of pure DMPC (23.9 degrees C) and a region of liquid-disordered-liquid-ordered coexistence (l(d)-l(o)) above the T(m). We first examined equilibrium binding and kinetics of amphiphile insertion into single-phase vesicles (s, l(d), and l(o) phase). The data obtained were then used to predict the behavior of the equivalent process in a two-phase system, taking into account the fractions of phases present. Next, the predicted kinetics were compared to experimental kinetics obtained from a two-phase system. We found that association of the amphiphile with lipid vesicles is not influenced by the existence of l(d)-l(o) phase boundaries but occurs much more slowly in the s-l(o) phase coexistence region than expected on the basis of phase composition.